Late presentation of a solitary metastasis of renal cell carcinoma as an obstructive duodenal mass. - Toh, S. K. (BMJ Group, 1996)
We present a rare case of late solitary metastasis of renal cell carcinoma presenting with duodenal obstruction. Metastatectomy resulted in relief of symptoms and may improve long-term survival.